Synthesis and characterization of new polyimides containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Halhalli, Mahadeo R.; Avadhani, C. V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2009)
A new unsymmetrical aromatic diamine, viz., 4-pentadecylbenzene-1,3-diamine was synthesized through a series of reaction steps starting from 3-pentadecylphenol. 4-Pentadecylbenzene-1,3-diamine was employed to synthesize a series of new polyimides by one-step polycondensation in m-cresol with four commercially available aromatic dianhydrides. viz., 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenone-tetracarboxylic dianhydride (BTDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6-FDA). Inherent viscosities of resulting polyimides were in the range 0.33-0.67 dL/g and number average molecular weights were in the range 14,700-52,200 (GPC, polystyrene standard). Polyimides containing pendent pentadecyl chains were soluble in organic solvents such as chloroform, m-cresol, N,N-dimethylacetamide (DMAc), 1-methyl-2-pyrrolidinone (NMP), pyridine and nitrobenzene. Strong and flexible films of polyimides could be cast from their chloroform solutions. Polyimides exhibited glass transition temperature in the range 158-206 degrees C. The temperature at 10% wt. loss (T(10)). determined by TGA in nitrogen atmosphere, of polyimides was in the range 470-480 degrees C indicating good thermal stability. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Cashew nut shell liquid; Glass transition temperature; Pendant pentadecyl chain; polyimides

Regularly alternating poly(amideimide)s containing pendent pentadecyl chains: synthesis and characterization - Sadavarte, Nilakshi V.; Avadhani, C. V.; Naik, Parimal V.; Wadgaonkar, Prakash P. (European Polymer Journal, 2010)
Two new aromatic diamines containing preformed amide linkages, viz., N,N'-(4-pentadecyl-1,3-phenylene)bis(4-aminobenzamide) I and N,N'-(4-pentadecyl-1,3-phenylene)bis(3-aminobenzamide) II, were synthesized by reaction of 4-pentadecylbenzene-1,3-diamine with 4-nitrobenzoylchloride and 3-nitrobenzoylchloride, followed by reduction of the respective dinitro derivatives. A series of new poly(amideimide)s was synthesized by poly-condensation of I and II with four commercially available aromatic dianhydrides, viz., pyromellitic dianhydride (PMDA), 4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA), and 4,4'-(hexafluoroisopropylidene)diphthalic anhydride (6-FDA) in N,N-dimethylacetamide (DMAc) employing conventional two step method via poly(amic acid) intermediate followed by thermal imidization. Reference poly(amideimide)s were synthesized by polycondensation of N,N'-(1,3-phenylene)bis(4-aminobenzamide) and N,N'-(1,3-phenylene)bis(3-aminobenzamide) with the same aromatic dianhydrides. Inherent viscosities of poly(amideimide)s containing pendent pentadecyl chains were in the range 0.37-1.23 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C indicating the formation of medium to high molecular weight polymers. The poly(amideimide)s containing pendent pentadecyl chains were found to be soluble in N,N-dimethylacetamide, N,N-dimethylformamide, 1-methyl-2-pyrrolidinone and pyridine and could be cast into transparent, flexible and tough films from their N,N-dimethylacetamide solution. Wide angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were essentially amorphous in nature. X-ray diffractograms also displayed sharp reflection in the small angle region (20 approximate to 3 degrees) for poly(amideimide)s containing pentadecyl chains indicating the formation of layered structure arising from packing of flexible pentadecyl chains. The glass transition temperatures observed for reference poly(amideimide)s were in the range 331-275 degrees C and those for poly(amideimide)s containing pendent pentadecyl chains were in the range 185-286 degrees C indicating a large drop in T(g), owing to the ``internal plasticization'' effect of pentadecyl chains. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, were in the range 460-480 degrees C indicating their good thermal stability. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Glass transition temperature; Pendent pentadecyl chain; Poly(amideimide)s; Preformed amide linkage; thermal stability

Synthesis and characterization of novel aromatic-aliphatic polyamides from bis-[(4-aminobenzyl)-4-benzamide] ether - Patil, A. S.; Medhi, M.; Sadavarte, Nilakshi V.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A novel aromatic diamine monomer containing preformed aromatic-aliphatic amide and ether linkage, bis-[(4-aminobenzyl)-4-benzamide] ether (BABE) was prepared from 2-phenylacetonitrile. BABE was characterized by FT-IR, (1)H NMR, (13)C NMR and mass spectrometry. Five new aromatic polyamides were prepared by low temperature solution polymerization from BABE and different mole proportions of isophthaloyl chloride (IPC) or terephthaloyl chloride (TPC). The resulting polymers were characterized by means of FT-IR, inherent viscosity [eta(inh)], solubility, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA] and X-ray diffraction [XRD]. Polyamides were obtained in good yields and had moderate to high molecular weights as indicated by inherent viscosities in the range 0.63-1.35 dL/g in (DMAc + 4% LiCl). XRD results showed the partly crystalline nature of polymers and these polymers dissolved in aprotic polar solvents containing LiCl. The solubility of copolyamides improved due to random placement of constituent IPC and TPC during polymerization. DSC analysis of these polyamides showed glass transition temperatures in the range of 197-204 degrees C, and they showed no weight loss below 336 degrees C when analyzed by TG. These polyamides have potential applications as engineering materials. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bis-[(4-aminobenzyl)-4-benzamide] ether; ether linkage; Inherent viscosity; polyamides; thermal stability; XRD

Synthesis and characterization of new organosoluble aromatic polyamides and polyazomethines containing pendent pentadecyl chains - Sadavarte, Nilakshi V.; Avadhani, C. V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2011)
New aromatic polyamides and polyazomethines containing pendent pentadecyl chains were synthesized by polycondensation of pentadecylbenzene-1,3-diamine with (i) four commercially available aromatic diacids, viz., biphenyl-4,4'dicarboxylic acid, 4,4'-oxybisbenzoic acid, terephthalic acid and isophthalic acid, and (ii) dialdehydes, viz., terephthaldehyde, isophthaldehyde and a 50 : 50 mol% mixture of terephthaldehyde, and isophthaldehyde, respectively. Inherent viscosities of polyamides and polyazomethines were in the range 0.35-0.56 dL g(-1) and 0.33-0.38 dL g(-1), respectively, indicating the formation of medium molecular weight polymers. The presence of pendent pentadecyl chains in polyamides and polyazomethines led to an improvement in their solubility in organic solvents. Polyamides could be cast into flexible, transparent and tough films from their solution in N,N-dimethylacetamide while polyazomethines could be solution cast into transparent, flexible and stretchable films from their CHCl(3) solution. (1)H-NMR studies based on amide proton signals and azomethine proton signals indicated the presence of constitutional isomerism in the polyamides and polyazomethines. Wide-angle X-ray diffraction patterns exhibited broad halo indicating that the polymers were amorphous in nature. X-ray diffractograms also displayed sharp reflections in the small angle region (2 theta approximate to 3 degrees) indicating the formation of layered structure arising from packing of flexible pentadecyl chains. The glass transition (T(g)) temperatures of polyamides were in the range 169-215 degrees C while T(g) values for polyazomethines were in the range 16-55 degrees C. The temperature for the 10% weight loss of polyamides and polyazomethines were in the range 430-460 degrees C and 425-440 degrees C, respectively, in a nitrogen atmosphere, which indicated their good thermal stability. Polyazomethines were also characterized by UV-Vis and photoluminescence spectroscopy and optical band gap (E(g)) values, calculated according to the maximum of the UV absorption, were found to be in the range 2.82-3.10 eV.
Keywords: High performance polymers; optical band gap; polyamides; polyazomethines; solubility

New organosoluble aromatic poly(esterimide)s containing pendent pentadecyl chains: synthesis and characterization - Sadavarte, Nilakshi V.; Patil, Sachin S.; Avadhani, C. V.; Wadgaonkar, Prakash P. (High Performance Polymers, 2013)
A new diimide dicarboxylic acid, namely 2,2-(4-pentadecyl-1,3-phenylene)bis(1,3-dioxoisoindoline-5-carboxylic acid), containing preformed imide rings and pentadecyl chain, was synthesized by the reaction of 4-pentadecylbenzene-1,3-diamine with trimellitic anhydride. A series of new aromatic poly(esterimide)s (PEIs) was synthesized using diphenylchlorophosphate-activated direct polycondensation of 2,2-(4-pentadecyl-1,3-phenylene)bis(1,3-dioxoisoindoline-5-carboxylic acid), with five commercially available bisphenols, namely 4,4-isopropylidenediphenol (I), 4,4-(hexafluoroisopropylidene)diphenol (II), 4,4-oxydiphenol (III), 4,4-biphenol (IV), and 4,4-(9-fluorenylidene)diphenol (V) in the presence of pyridine and lithium chloride. Inherent viscosities of PEIs were in the range 0.54-0.83dLg(-1) in chloroform (CHCl3) at 30 +/- 0.1 degrees C. PEIs containing pendent pentadecyl chains were soluble in organic solvents such as CHCl3, m-cresol, N, N-dimethylacetamide, 1-methyl-2-pyrrolidinone, pyridine, and nitrobenzene. Tough, transparent, and flexible films of PEIs could be cast from their CHCl3 solutions. PEIs exhibited glass transition temperature in the range 145-198 degrees C. The temperature at 10% weight loss of PEIs, determined by thermogravimetric analysis under the nitrogen atmosphere, was in the range of 450-470 degrees C indicating good thermal stability.
Keywords: pendent pentadecyl chains; Polycondensation; Polyimide; Preformed imide rings; Thermogravimetric analysis

Functionalization of cardanol: towards biobased polymers and additives - Voirin, Coline; Caillol, Sylvain; Sadavarte, Nilakshi V.; Tawade, Bhausaheb V.; Boutevin, Bernard; Wadgaonkar, Prakash P. (Polymer Chemistry, 2014)
Among the renewable resource materials, cashew nut shell liquid (CNSL) is considered as an important starting material due to its unique structural features, abundant availability and low cost. A large number of chemicals and products have been developed starting from CNSL by taking advantage of the three reactive sites, namely, phenolic hydroxyl, aromatic ring and unsaturation(s) in the alkenyl side chain. This comprehensive review deals with general information on CNSL, its purification and separation methods, reactivity and applications in polymer chemistry.

Step-growth polymers from cashew nut shell liquid (CNSL)-based aromatic difunctional monomers - Chatterjee, Deepshikha; Sadavarte, Nilakshi V.; Shingte, Rahul D.; More, Arvind S.; Tawade, Bhausaheb V.; Kulkarni, Arun D.; Ichake, Amol B.; Avadhani, C. V.; Wadgaonkar, Prakash P. (Cashew Nut Shell Liquid, 2017)
Cashew nut shell liquid (CNSL) is an attractive renewable resource material which is available in abundance (44,50,000 tonnes worldwide and 7,53,000 tonnes in India in 2013) at low cost (around 0.27 $/kg in 2015) and is mainly composed of anacardic acid, cardanol, cardol and 2-methyl cardol. Cardanol is obtained as a major product during hot oil extraction or roasting process of CNSL. Cardanol possesses interesting structural features. The aromatic ring of cardanol can undergo electrophilic substitution reactions; the unsaturated side chain can undergo epoxidation, hydrogenation, metathesis, etc., while the phenolic hydroxyl group can undergo various reactions such as esterification and alkylation. Such opportunities of chemical modifications offered by cardanol have been extensively explored to synthesise a range of interesting aromatic difunctional monomers that have subsequently been utilised to prepare a host of step-growth polymers. Summarised herein are research efforts that have contributed towards the synthesis of step-growth polymers based on aromatic difunctional monomers derived from cardanol. The properties of high-performance polymers, with a particular focus on processability and thermal characteristics, are highlighted.